Gait parameters in a sample of healthy Colombian adults aged between 18 and 25 years: a cross-sectional study. - Duque-Ramírez, José Ricardo; Vélez-Uribe, José David; Gómez-Suárez, Nicolás Eugenio; Manrique-Hernández, Rubén Darío (Revista Facultad de Medicina de la Universidad Nacional de Colombia)
Introduction: Gait analysis is fundamental for assessing the functional capacity and motor skills of any individual. Therefore, a reliable and specific analysis method is necessary to study gait in different populations. However, the reference values of gait parameters currently used in Colombia come from studies conducted on population groups from other countries or regions. Objective: To identify the reference values of gait kinematic parameters in healthy Colombian young adults. Materials and methods: A quantitative, descriptive, and cross-sectional study was conducted. The sample consisted of 155 Colombian young adults (aged 18 to 25). Temporal-spatial parameters and kinematics data of each participant were measured through 3D motion capture, which was performed using 8 infrared cameras (Bonita 10) and the VICON NEXUS 1.8.5. software. POLYGON 4.1. software was used for data analysis, and statistical analysis was performed using the STATA 12.1. software package. Results: Average age, height and BMI were 20.3 years, 1.66m and 21.91T kg/m², respectively. 41.29% of participants were male. The average values obtained for the cadence, stride time, speed and initial swing temporal-spatial parameters were as follows: 103 steps/min, 1.16 seconds, 1.01 m/s, and 59.62% of the gait cycle (both sides), respectively. Conclusion: Normal gait kinematic and temporal-spatial parameters of a group of healthy Colombian young adults were obtained, which will allow establishing the characteristics of normal gait in this population, improving intervention strategies, and designing and implementing technical aids aimed at improving locomotion in Colombian individuals.